To Stay or to Leave? How Ethical Climates and Leadership Styles Influence Gen Z Turnover Intention - Alice Salendu; Shofi Nadia; Safira Hanun Nabila; Safira Dwi Tyas Putri; Aditya Wira Pahlawan (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2025)
Generation Z values inclusive and supportive workplaces but often exhibits high turnover intention. This study examines how transformational and servant leadership influence turnover intention among Gen Z employees in Indonesia, with caring and self-interest ethical climates as mediators. A cross-sectional survey of 314 Gen Z employees was analyzed using structural equation modeling (SEM). Results show that caring ethical climate did not significantly relate to turnover intention or mediate the leadership–turnover link. In contrast, self-interest ethical climate showed a strong positive relationship with turnover intention and served as a significant mediator. These findings indicate that servant leadership is more effective than transformational leadership in reducing Gen Z turnover intention by diminishing self-interest ethical climate, while caring ethical climate may have limited relevance across generations.